Mr. Calvino(s): a dynamic character and the dinamics of a character. - Martins, Ana Isabel Correia (Revista de Letras, 2019)
Gonçalo M. Tavares, in his colectanea, summon to The neighborhood several historical figures – philosophers, poets, novelists, play writers – that catapulted from reality into fictional coexistence. The affinities – onomastic, thematic, esthetical and literary – with real personalities do not prevent the narrative development neither the autonomy of each of the neighbors. Sir Calvino appears in the reminiscence of Italo Calvino, the author of Invisible Cities, though a metaleptical process of ontological transposition. The character conquers is own space, constructs his own fictional existence, emancipating his genealogy and finally exhibiting his own personality and dynamic. The present work aims to study this transliterary movement, comparing the Invisible Cities and The Neighborhood, deepening the dialogue between their protagonists: desires, anguishes and expectations.